Mendobrak Dominasi Sejarah: Upaya Laboratorium Banten Girang (LBG) dalam Mengenalkan Kembali Sejarah Pra-Islam dan Tinggalannya di Banten - Nilam Gita Perdana (Umbara, 2020)
Banten has experienced long chronological history that shaped its society’s culture today. This study discusses activities by a community named “Laboratorium Banten Girang” (known as LBG) in Serang, Banten. The community aims at introducing a non-dominant history in Banten, and at the same time promote it as cultural heritage into the public space. In this study, the history of Banten presented in two sections; dominant and non-dominant history. Data in this study were collected through observation and in-depth interviews to members of the LBG, and residents living in the historical site of Banten. Results of this study suggests that LBG brings discourse outside the official or authorized discourse of the dominant history and try to introduce the other side of the story of Banten history; dating back to pre-Islamic history and its heritage. In their activities, the LBG do not aim to repair or to beautify the existing heritage and history, but they reintroduce it through various activities instead. Their effort receive diverse responses from society both rejection and acceptance. Meanwhile, the discourse carried by LBG indirectly serves as a non-physical revitalization project on cultural heritage and an effort to realize the ideas of the advancement of Banten’s culture.